(untitled) - Tabb, William K. (New York, 1995)
The Postwar Japanese System succeeds in placing the economic "miracle" in its proper social and political framework. A broad, intelligent overview of the Japanese political economy, the book suggests important implications for the United States in the story of Japan's prosperity and current distress. It will be a key resource for all those interested in Japanese society.